(untitled) (Research, Society and Development, 2019)
This article aims to present a didactic sequence (SD) that was developed in a Pre-Kindergarten class at a private school in Santa Maria, RS. The study was conducted in the second half of 2018, with thirteen children in the 4-year-old age group. As an investigative approach, the study is characterized as an action research and constitutes a cut-off of the Master’s Dissertation in Teaching Humanities and Languages, elaborated by the first author. The theoretical framework is based on documents related to Early Childhood Education, research focus and authors such as: Morin (1999 and 2011); Nóvoa (2009); Oliveira (2011 and 2014); Cancian & Goelzer (2016); Rinaldi (2017), among others. With the report of this experience, it was possible to observe that in Early Childhood Education, it is necessary to take into account attentive listening of what children indicate they want to know at every moment, as open channels to learn it. For this, it requires the teacher an educational intentionality with the children, to know how to progress to reach them, harmonizing teaching and learning.